Comparison of surgical resection and radiofrequency ablation for stages I and II elderly hepatocellular carcinoma patients (≥ 65 years): A SEER population-based propensity score matching’s study - Xie, Qingqing; Yang, Yongwen; Qu, Bin; Xiao, Ping; Tang, Faqing; Shen, Haoming (Frontiers in Oncology, 2022)
Background: The treatment for hepatocellular carcinoma (HCC) remains controversial and limited in elderly patients. Therefore, we aimed to explore treatment choices for the elderly patients (≥65years) following surgical resection (SR) versus radiofrequency ablation (RFA) with HCC (single lesion less than 5cm). Methods: Using SEER database to identify HCC patients who receiving treatment of SR/RFA. Kaplan‐Meier method and Cox proportional hazards regression method were used to determine the prognostic factors associated with overall survival (OS) and disease-specific survival (DSS). In addition, RFA group and SR group patients were matched with 1:1 propensity score matching (PSM) for diagnosis age, sex, race, marital, AJCC, grade, radiotherapy, and chemotherapy to decrease the possibility of selection bias. Conditional disease-specific survival (CS) was estimated using the life-table method. Results: A total of 794 patients underwent SR and 811 patients underwent RFA were confirmed from the SEER database. Surgery type was an independent risk factor for HCC. Survival analysis indicated that SR, races, AJCC I, no chemotherapy treatment, and Grade I were cumulative risk factors that can significantly improve median survival for HCC(P<0.05). After PSM analysis, only surgery type was significantly improved median survival of HCC patients (SR vs. RFA, HR: 0.644, 95%CI: 0.482–0.86; P<0.001). For RFA group, the 2 -, 3 -, and 5-year CS rates were approximately 71%, 65%, and 62%, respectively, and corresponding to 82%, 80%, and 78% in the SR group. Conclusions: SR treatment can provide survival benefits for elderly patients of＜5 cm single lesion HCC.